Molecular identification and species richness of flies (diptera) and their associated Bovidae hosts at cattle farms in Selangor, Malaysia - Yaakop, Salmah; Amiruddin, Puteri Amira; Mohammed, Muhamad Azmi; Badrulisham, Aqilah Sakinah; Zulkifli, Nadiatur Akmar; Mohd Nadzir, Mohd Noor Hisham (Universiti Putra Malaysia Press, 2022)
Flies (Diptera) play a significant role in the ecosystem as pollinators and decomposers, and they are also important vermin and disease vectors. Studies on the dipteran species are still lacking in Malaysia; therefore, the dipteran species’ biology, morphology, distribution, and abundance are necessary. The objectives of this study were to identify dipteran species using a molecular approach, determine flies’ Bovidae hosts, and investigate the diversity of the fly’s species at three different cattle farms purposively selected in Selangor, Malaysia. The fly species were identified using cytochrome oxidase subunit I (COI) (Haematopota javana, Tabanus rubidus, Tabanus fontinalis, Iranihindia martellata, Musca domestica, and Chrysomya megacephala), while another six species only up to genus level ( Haematopota sp. 1, Musca sp. 1, Asilus sp., Metopia sp., Anasillomos sp., and Ommatius sp.). In addition, two species of hosts: Bos indicus and Bos taurus, were proven to be the associated host species for the dipteran species based on molecular data of cytochrome b (cytb). However, there were no significant differences between farms in species diversity and richness (F = 1.262, df = 2, p = 0.2459 >0.05). Interestingly, the two most dominant dipteran genera collected from the cattle farms were Musca and Chrysomya. At the same time, its abundance may have been influenced by the structure of the cattle cage flooring, which serves as a breeding site and food source. These findings contribute to fundamental epidemiological data in developing control strategies for dipteran species and are of great economic and health importance to livestock production in Malaysia.